Dampak Bantuan Sarana Perikanan Tangkap Terhadap Peningkatan Pendapatan Nelayan Di Kabupaten Gianyar Provinsi Bali - Arnawa, Ketut; Purnama, Ida Bagus; Arisena, Mekse Korri (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 4 No 1 (2016), 2016)
Main points of the purpose of this study was to determine the impact of the help facilities capture fisheries to increase the income of fishermen in Gianyar Regency. Research location is determined purposive sampling in the  Lebih village. To determine the impact of providing assistance to the income of fishermen fishing tools used production function Cobb-Douglas model. The results found, assisting in the capture fishery means to increase the income of fishermen of 2.6287% did not differ significantly. Factors had significant effect on the income of fishermen is type  of boat and cost. Factors not significant effect on the income of fishermen is, age, education,  fishing tools type, distance traveled, and long sea
Keywords: fishing, income, cost, fishing tools, fishing, boat